Emotional Intelligence among Undergraduate Nursing Students in Selected Colleges of Morang District, Nepal - Pradhan, Uma; Koirala, Namu; Shrestha, Menuka; Baral, Dharani Dhar; Parajuli, Surya B. (Birat Journal of Health Sciences, 2021)
Introduction: Emotional Intelligence (EI) is the ability to recognize one's own and other's emotions and capacity to utilize the emotional information to adjust to the environment. Nurse with high EI is found to have a better interpersonal relationship, higher job satisfaction, better leadership abilities, and better academic achievement. There is a gap in information regarding EI in nursing students of Morang district. Objective: The objective of the study was to find out the emotional intelligence and its association with selected socio-demographic variables among undergraduate nursing students of selected colleges of Morang district, Nepal. Methodology: This was a cross-sectional study carried out from June 2020 to November 2020 among 423 undergraduate nursing students of Purbanchal University School of Health Sciences, Hamro School of Nursing and Koshi Health and Science Campus. Ethical clearance was obtained from Purbanchal University School of Health Sciences- Institutional Review Committee (PUSHS-IRC) and informed consent were taken from study participants. A standard tool, “The Schutte Self Report Emotional Intelligence Test (SSEIT)” was used. Data was collected through a google form. Univariate and bivariate analysis was performed. P-value <0.05 at 95% confidence interval was considered statistically significant for bivariate analysis. Results: Majority (75.4%) of nursing students had a high level of EI score and 24.6% of the students had a moderate level of EI score. There was no statistically significant association of total EI score with any of the selected demographic variables. Further, the selected domains such as perception of emotion with an academic year of study (p=0.02), occupation of the mother (p=0.017), management of other's emotions with a year of the study (p=0.018), and utilization of emotion with the type of schooling (p=0.003) were statistically significant. Conclusion: Emotional intelligence was high and does not vary with different sociodemographic characteristics among nursing students.